The Development of Pop Up 3D General Map Using Discovery Learning Models to Improve Creativity and Learning Outcomes of Social Studies Grade V Elementary School - Ningsih, Wahyu Kurnia; Riyanto, Yatim; Suyanto, Totok (International Journal for Educational and Vocational Studies, 2019)
The researcher was interested in developing learning media "3D Pop Up general map". This study aims to develop a 3D Pop Up general map media and describe the feasibility and effectiveness of improving the creativity and learning outcomes of social studies material in the Indonesian geographical characteristics of grade V elementary school. This research was conducted in Ujung IX/ 34 SDN, Semampir, Surabaya in the second semester of the 2018-2019 academic year. The development of learning media in this study uses a 4-D model. In this study used instruments in the form of validation sheets, student activity observation sheets during learning, teacher and student response questionnaires to the media, student learning creativity observation sheets, and learning outcomes tests, affective and psychomotor observation sheets. The results of the study show: (1) the learning media developed meet the criteria: (a) the validity shown through the validator's assessment of the learning media is very good; (b) feasibility is shown through teacher and student responses to positive media questionnaires; (c) effectiveness, indicated by student activities in learning in the ideal time span, observations of student learning creativity when learning increases, completeness of cognitive, affective and psychomotor learning outcomes also increases. Thus the "3D Pop Up general map" can be used as an alternative to social studies learning in the fifth grade of elementary school.